2015
DOI: 10.1186/s12879-015-1265-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral therapy and retention in care for adolescents living with HIV from 10 districts in Uganda

Abstract: BackgroundAdolescents have gained increased attention because they are the only age group where HIV related mortality is going up. We set out to describe the level and factors associated with adherence to antiretroviral therapy (ART) as well as the 1 year retention in care among adolescents in 10 representative districts in Uganda. In addition, we explored the barriers and facilitators of adherence to ART among adolescents.MethodsThe study involved 30 health facilities from 10 representative districts in Ugand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
201
9
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(238 citation statements)
references
References 32 publications
23
201
9
5
Order By: Relevance
“…As with previous studies, stigma was reported to impact on ART adherence especially among adolescents in boarding schools [20,23,37,38]. These findings corroborate other studies reporting the challenges faced by ALWHA in schools including discrimination from their peers and educators suggesting an increasing need for sensitization and training on their rights and special needs in school settings [23,38].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As with previous studies, stigma was reported to impact on ART adherence especially among adolescents in boarding schools [20,23,37,38]. These findings corroborate other studies reporting the challenges faced by ALWHA in schools including discrimination from their peers and educators suggesting an increasing need for sensitization and training on their rights and special needs in school settings [23,38].…”
Section: Discussionsupporting
confidence: 89%
“…The pivotal role of health-care providers and the clinic environment to ALWHA is well known, with various studies showing the need for supportive early disclosure to caretakers [42–44], provision of adolescent friendly services [45], role of peer groups [20,45,46] and support for gradual transition to adult based care [45,46]. Despite this information, lack of clear guidelines and support was associated to late, incomplete and poor disclosures by caretakers and the subsequent decline in adherence [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatedly, it is well documented that stigma is a key reason why adolescents do not want to disclose HIV status to their peers, as adolescence is a time when positive self-image and acceptance are some of the biggest considerations as adolescents build their network of peers and find their footing in the community [22]. As Suubi + Adherence is a combination intervention that integrates matched savings, financial education, and life skills for adolescents receiving the treatment, it is possible that participation in these program components provided ALWHA exposure to other adolescents with the same status and life circumstances, promoting confidence and alleviating perceived stigma on ART usage.…”
Section: Discussionmentioning
confidence: 99%